2014
DOI: 10.1111/dmcn.12589
|View full text |Cite
|
Sign up to set email alerts
|

The influence of early modified constraint‐induced movement therapy training on the longitudinal development of hand function in children with unilateral cerebral palsy

Abstract: AHAAssisting Hand Assessment MCA Middle cerebral artery mCIMT Modified constraint-induced movement therapy WDMI White matter damage of immaturity AIM There is evidence that modified constraint-induced movement therapy (mCIMT) has a short-term positive effect on hand function in children with unilateral cerebral palsy (CP), but the long-term effect is unknown. The aim of this study was to investigate whether or not a single block of mCIMT (2h/d for 2mo) at age 2 to 3 years influences the course of development o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
30
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 25 publications
(79 reference statements)
0
30
0
1
Order By: Relevance
“…In a small study using various assessments of hand function, stable ability was seen over a 6-year period at 10 to 21 years of age. 15 Future studies that explore long-term development in relation to various factors that are assumed to affect the development of hand function in children with unilateral CP would supplement the predictive and prognostic information provided in this study. 13 Thus, further studies of development of hand function at older ages are needed -as indicated by the fact that contractures of the forearm are not commonly reported before 12 years of age, 14 although a limited active range of motion is present at an early age.…”
Section: Discussionmentioning
confidence: 87%
“…In a small study using various assessments of hand function, stable ability was seen over a 6-year period at 10 to 21 years of age. 15 Future studies that explore long-term development in relation to various factors that are assumed to affect the development of hand function in children with unilateral CP would supplement the predictive and prognostic information provided in this study. 13 Thus, further studies of development of hand function at older ages are needed -as indicated by the fact that contractures of the forearm are not commonly reported before 12 years of age, 14 although a limited active range of motion is present at an early age.…”
Section: Discussionmentioning
confidence: 87%
“…21 A large proportion of the children with unilateral CP in our study had performed intensive training, and it is unknown whether this has influenced the developmental trajectories. 23 And for children with bilateral CP, the effect of hand training is unknown. 17,22 Despite knowledge of treatment effects, the long-term effects of intensive hand training for children with unilateral CP is inconclusive.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of brain lesion on intervention outcome is rarely considered. One study demonstrates that one block of CIMT at age 2-3 years can predict better longitudinal development of bimanual hand use, but this treatment effect diminishes when controlling for brain lesion and baseline ability (Eliasson & Holmefur, 2014); in other studies of older children, the results are inconclusive (Islam et al, 2014;Kuhnke et al, 2008). The present retrospective cohort design including only one measure of the children's hand function could be seen as a weakness, because it does not establish a causal effect to the extent of an experimental design.…”
Section: Discussionmentioning
confidence: 99%